2015
DOI: 10.3892/etm.2015.2671
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar button-electrode plasma vaporization of the prostate: An effective option for patients with post-brachytherapy retention

Abstract: Urinary retention is a common urinary complication following brachytherapy for prostate cancer. When conservative therapy has failed, surgical intervention, such as transurethral resection of the prostate (TURP), is performed. In the present case, it was found that conventional bipolar TURP was an inappropriate choice of therapy, since the electrical loop could easily rupture and discharge sparks when encountering the seeds intraoperatively; however, bipolar button-electrode plasma vaporization of the prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been shown that BPV is a low morbidity procedure with functional short-to mid-term results comparable or even superior to conventional transurethral resection of the prostate (TURP) [3][4][5][6][7][8][9]. However, long-term results following BPV, which are needed to prove the durability of symptom improvement and eventually non-inferiority compared to conventional TURP are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that BPV is a low morbidity procedure with functional short-to mid-term results comparable or even superior to conventional transurethral resection of the prostate (TURP) [3][4][5][6][7][8][9]. However, long-term results following BPV, which are needed to prove the durability of symptom improvement and eventually non-inferiority compared to conventional TURP are lacking.…”
Section: Introductionmentioning
confidence: 99%